Extraction with environmentally friendly solvents - Płotka-Wasylka, Justyna; Rutkowska, Małgorzata; Owczarek, Katarzyna; Tobiszewski, Marek; Namieśnik, Jacek (TrAC, Trends in analytical chemistry (Regular ed.), 2017)
The ever-increasing demand for determining compounds at low concentration levels in complex matrices requires a preliminary step of analytes isolation/enrichment in order to employ a detection technique characterized by high sensitivity at low LOQ. Sample preparation is considered as crucial part of analytical procedures. Previously the parameter of “greenness” is as important as selectivity in order to avoid using harmful organic solvents in sustainable extraction techniques. These solvents can generate hazardous, toxic waste while consuming large resources volume. Developing new green solvents is one of the key subjects in Green Chemistry in order to reduce the intensity of anthropogenic activities related to analytical laboratories. A lot of new, more eco-friendly media have been employed as extractant phases. These media, besides of being more eco-friendly, provide shorter extraction times, simplicity, low cost, better selectivity in some cases. The most promising, most widely used green extraction solvents are described in this review. •Replacement of VOCs by eco-friendly solvents is becoming increasingly important.•Several new solvents have been developed and introduced in analytical practice.•Solvents environmental impact assessment is becoming increasingly important.•Analytical chemistry requires solvents “greenness” assessment systems to be comprehensive.